Safety And Effectiveness Of Three-Port Laparoscopic Cholecystectomy: A Retrospective Comparative Study - ( MS), Vivek Kumar; singh, Prakhar; Khandelwal, Shivam; Husain, Mohd Zafar (Journal of Neonatal Surgery, 2025)
Background Laparoscopic cholecystectomy (LC) is the gold-standard treatment for symptomatic cholelithiasis. Conventional four-port LC (4PLC) offers excellent ergonomics but at the expense of an additional incision. Three-port LC (3PLC) seeks to minimise access trauma while preserving operative safety. Evidence on its real-world performance in South-Asian tertiary centres remains limited. Methods We retrospectively analysed 200 consecutive elective LCs performed between March 2021 and March 2023 at Sarojini Naidu Medical College, Agra. One hundred patients underwent 3PLC (Group 1) and 100 underwent 4PLC (Group 2). Demographics, operative details, conversions, complications, length of stay (LOS) and 30-day outcomes were compared. Statistical analysis employed χ², Student’s t-test or Mann–Whitney U where appropriate (p < 0.05 significant). Results Group 1 comprised 77 females/23 males (mean 53 ± 12.8 years); Group 2, 82 females/18 males (mean 51.3 ± 12.9 years). Operative time was similar (31.0 ± 9.1 min vs 31.6 ± 7.6 min; p = 0.63). In Group 1, nine patients (9 %) required a fourth port and one (1 %) required conversion to open surgery owing to dense adhesions; no conversions occurred in Group 2. Overall complication rates were comparable (2 % vs 2 %; p = 1.0). Median LOS for both groups was 1 day (range 1–2). Multivariate analysis identified gallbladder edema, prior upper-abdominal surgery and intra-operative cholecystitis as independent predictors of longer operative time irrespective of port number. Conclusion Three-port LC is a safe, feasible and cost-saving alternative to conventional 4PLC when performed by experienced surgeons, with equivalent operative time, morbidity and LOS. The procedure can be commenced with three ports and seamlessly escalated by adding a fourth port or converting to open surgery when warranted.